Reference group and utilitarian shopping motivation and online purchase decision of fashion products in Tokopedia Marketplace - Muhammad Rayhan Fauzan; Gugyh Susandy (Universitas Negeri Padang, 2021)
This study aims to determine the influence of reference groups and utilitarian shopping motivation on Online purchase decisions for fashion products on Tokopedia. The independent variable (X) examined in this study is the Reference Group (X1) and Utilitarian Shopping Motivation (X2) and the dependent variable (Y) is the Online Purchase Decision. The method using in this research is descriptive survey research methods and explanatory surveys with descriptive and verification research types. Data collection techniques using questionnaires, observation, and literature study. The sample selection by purposive sampling technique with a sample of 100 respondents. This study uses the SPSS 22 application, using multiple regression analysis, the research results show that partially and simultaneously the Reference Group and Utilitarian Shopping Motivation has an effect on Online Purchasing Decisions. Further research is suggested to examine other variables not examined in this study, such as brand image, or brand loyalty and can also be done by replacing the unit of analysis with another marketplace.